Change readiness in individuals experiencing homelessness and multiple complex needs. Issue 1 (7th May 2021) - Lord, Alex; Tickle, Anna; Buckell, Anna
Abstract : Purpose: This study aims to understand how staff in homelessness services conceptualise readiness for change in the individuals they support and how this informs their decision-making in practice. Design/methodology/approach: A qualitative design was used. Ten staff members participated in semi-structured interviews. Data were examined through inductive–deductive thematic analysis, using a social constructivist epistemological lens. Findings: Five main themes were constructed: "multiple complex needs mean multiple complex changes", "talk versus behaviour", "change is not a linear trajectory", "the role of consistent boundaried relationships" and "change is not solely within the individual's control". Practical implications: This research challenges existing notions of "readiness for change" as located within individuals and a prerequisite for using support from services. It has implications for staff and services, particularly those which are time-limited and address only single problems; service users may not be ready for some changes, but it should not be assumed they are not ready for change in other areas of their life. The offer of supportive relationships may precede and contribute to readiness for positive changes. Support should be offered based not only an individual's intra-psychic readiness for change but also how the system might actively work to promote hope that change can be achieved and maintained. Originality/value: To the best of the authors' knowledge, this is the first study to explore staff members' conceptualisations of readiness to change in relation to individuals with multiple complex needs and how this might influence practice.